Monthly range of adolescent orangutans (Pongo pygmaeus wurmbii) based on fruit availability in Tuanan Orangutan Research Station, Central Kalimantan, Indonesia - FAJAR SAPUTRA; DYAH PERWITASARI- FARAJALLAH; SRI SUCI UTAMI- ATMOKO; TOMI ARIYANTO; MARIA A. VAN NOORDWIJK (Biodiversitas Journal of Biological Diversity, 2017)
Setyawan. 2017. Monthly range of adolescent orangutans (Pongo pygmaeus wurmbii) based on fruit availability in Tuanan Orangutan Research Station, Central Kalimantan, Indonesia. Biodiversitas 18: 1445-1452. Adolescent orangutans become competitors with mothers supporting newborn infants. Thus, adolescent orangutans must coordinate with other orangutans in order to find fruit. How adolescent orangutans respond is reflected in the size and utilization of their home range area. The aims of our research were to determine (i) fruit availability, as an important component of orangutan diet, (ii) and the effect of fruit availability on home range use by adolescent orangutan. This research was conducted from August 2013 to July 2014 in Tuanan Orangutan Research Station, Central Kalimantan. The fruit trail method was used to estimate abundance of fruits (both from trees and lianas).Fallen fruit on census trails was assessed once per month, while focal animal sampling was used to estimate the home range by tagging a GPS point every 30 minutes during the tracking of an orangutan. In total, 62 tree and 15 liana species included in the known orangutan diet were fruiting during this study period. The highest period of fruit abundance for orangutan food occurred in November until January. Adolescent orangutans responded by increasing their monthly ranging area during this time of high fruit availability and decreased their range when fruit availability was low. Adolescent orangutans often used areas in their monthly range that had a high to medium abundance of fruit trees. When the number of trees bearing fruit decreased (low period), adolescent orangutans changed their monthly range to areas that consisted of medium to high abundance of liana fruit. Their ranging strategy optimized use of low quality habitat in order to survive in degraded forests.